2018
DOI: 10.1016/j.bbrep.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of AQP11-null kidney: Proximal tubular type polycystic kidney disease

Abstract: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is caused by the mutation of polycystins (PC-1 or PC-2), in which cysts start from the collecting duct to extend to all nephron segments with eventual end stage renal failure. The cyst development is attenuated by a vasopressin V2 receptor antagonist tolvaptan which, however, will not affect proximal tubule cysts devoid of V2 receptor. Aquaporin-11 (AQP11) is expressed selectively in the proximal tubule of the kidney and AQP11-null kidneys have a disruptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In addition, PSP/REG Iα has been demonstrated to increase β cell growth and regeneration by inducing cellular proliferation. PSP/REG Iα messenger ribonucleic acid (mRNA) is mainly found in the pancreas, but its expression has also been detected in the gastric mucosa and the kidneys [9,12]. It has been found in the urine and renal calculi of healthy individuals [13], which suggested a physiological role of PSP/REG Iα in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSP/REG Iα has been demonstrated to increase β cell growth and regeneration by inducing cellular proliferation. PSP/REG Iα messenger ribonucleic acid (mRNA) is mainly found in the pancreas, but its expression has also been detected in the gastric mucosa and the kidneys [9,12]. It has been found in the urine and renal calculi of healthy individuals [13], which suggested a physiological role of PSP/REG Iα in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of renal mRNAs have suggested that cell proliferation, remodeling of the extracellular matrix, apoptosis, and ER stress are possibly involved in the pathogenesis of the kidney injury [12] . Analytical studies of proteins in Aqp11 -/- mice have shown that decreased levels of mitochondrial proteins are likely associated with kidney injury due to AQP11 deficiency [13] . Previously, our group has demonstrated that in Aqp11 sjds/sjds mice the renal level of superoxide was increased and that an antioxidant ameliorated the reactive oxygen species (ROS)-related kidney injury in Aqp11 sjds /+ mice [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Capillary electrophoresis-mass spectrometry (CE-MS) Kaiser et al (2003), Wittke et al (2003), Metzger et al (2010), Alkhalaf et al (2010), Rossing et al (2008), Good et al (2010), Mischak, Delles, Klein, and Schanstra (2010) Tandem mass tag (TMT) Saito, Tanaka, Morishita, and Ishibashi (2017) single-cell genomics, transcriptomes, and protein abundance from comparable individual cells will provide substantial additional insight into the regulation of homeostatic and pathologic cell phenotype and function (Macaulay, Ponting, & Voet, 2017). Zhou et al (2019) demonstrated that integrating single cell RNA-seq, single cell DNA methylation analysis, and single cell combined displacement preamplification and PCR amplification (MALBAC) wholegenome sequencing revealed the molecular dynamics in an in vitro model of human implantation (Zhou et al, 2019).…”
Section: Proteomics Referencesmentioning
confidence: 99%